High-performance PbS quantum dot vertical field-effect phototransistor using graphene as a transparent electrode - Che, Yongli; Zhang, Yating; Cao, Xiaolong; Song, Xiaoxian; Zhang, Haiting; Cao, Mingxuan; Dai, Haitao; Yang, Junbo; Zhang, Guizhong; Yao, Jianquan (Applied physics letters, 2016)
Solution processed photoactive PbS quantum dots (QDs) were used as channel in high-performance near-infrared vertical field-effect phototransistor (VFEpT) where monolayer graphene embedded as transparent electrode. In this vertical architecture, the PbS QD channel was sandwiched and naturally protected between the drain and source electrodes, which made the device ultrashort channel length (110 nm) simply the thickness of the channel layer. The VFEpT exhibited ambipolar operation with high mobilities of μ e = 3.5 cm2/V s in n-channel operation and μ h = 3.3 cm2/V s in p-channel operation at low operation voltages. By using the photoactive PbS QDs as channel material, the VFEpT exhibited good photoresponse properties with a responsivity of 4.2 × 102 A/W, an external quantum efficiency of 6.4 × 104% and a photodetectivity of 2.1 × 109 Jones at the light irradiance of 36 mW/cm2. Additionally, the VFEpT showed excellent on/off switching with good stability and reproducibility and fast response speed with a short rise time of 12 ms in n-channel operation and 10.6 ms in p-channel operation. These high mobilities, good photoresponse properties and simplistic fabrication of our VFEpTs provided a facile route to the high-performance inorganic photodetectors.